Analysis of mathematics education from a STEAM approach at secondary and pre-universitary educational levels: A systematic review - Martín-Cudero, Daniel; Cid-Cid, Ana Isabel; Guede-Cid, Rocío (Journal of technology and science education, 2024)
Society is in an incessant process of reflection but the educational system is not following the same path, creating an urgent need for a quality educational renovation in which new methodologies, approaches and educational resources are developed based on creation, collaboration and learning by doing. In this sense, the integrated education of science, technology, engineering, art, and mathematics (STEAM) is postulated as an educational approach through which to transform the teaching-learning processes into processes that contribute to the development of critical, creative, and scientific thinking. Proof of this is the continuous increase in publications in this line of research. This article presents a systematic review with a total of 19 studies published in high-impact journals with the aim of making a critical reflection and evaluating the real scope of incorporating STEAM projects in education to improve the students' mathematical skills. In particular, five areas of interest have been evaluated: active learning in the teaching of STEAM subjects, the development of technological resources, the design and implementation of educational proposals, the evaluation of STEAM education and teacher training in STEAM education. Considering the results, we emphasize the need to continue working on the theoretical foundation and educational practice of this approach to allow teachers to implement it effectively.